Cover Image, Volume 31, Issue 3. (14th February 2018) - Paul, Katharina; Huelnhagen, Till; Oberacker, Eva; Wenz, Daniel; Kuehne, André; Waiczies, Helmar; Schmitter, Sebastian; Stachs, Oliver; Niendorf, Thoralf
Abstract : The cover image, by Katharina Paul et al., is based on the Research Article Multiband diffusion‐weighted MRI of the eye and orbit free of geometric distortions using a RARE‐EPI hybrid, DOI:10.1002/nbm.3872 . The authors would like to thank Oliver Stachs, University of Rostock for his support of the publication of this cover. Photo Credit: Celal Özerdem, The Berlin Ultrahigh Field Facility (B.U.F.F.) at the Max Delbrück Center.